2004
DOI: 10.3171/jns.2004.100.3.0389
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of motor evoked potentials compared with somatosensory evoked potentials and microvascular Doppler ultrasonography in cerebral aneurysm surgery

Abstract: Monitoring of MEPs is superior to SSEP monitoring and MDU in detecting motor impairment, particularly that from subcortical ischemia. Microvascular Doppler ultrasonography is superior to EP monitoring in detecting inadvertent vessel occlusion, but cannot assess remote collateral flow. Motor evoked potentials are most sensitive to all other intraoperative conditions and have a direct influence on the course of surgery in the majority of events. A controlled study design is required to confirm the positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
112
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(118 citation statements)
references
References 48 publications
5
112
1
Order By: Relevance
“…However, they noted that MEPs elicit patient movement, and they emphasized the need for communication to coordinate brief surgical pauses for MEP monitoring to avoid potential movement during microsurgery. Other authors have reported difficulty in consistently obtaining transcranial MEP responses in the lower extremities without using a stimulus intensity that produces unacceptable twitching artifact (6,20); this did not seem to be problematic in our patients.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…However, they noted that MEPs elicit patient movement, and they emphasized the need for communication to coordinate brief surgical pauses for MEP monitoring to avoid potential movement during microsurgery. Other authors have reported difficulty in consistently obtaining transcranial MEP responses in the lower extremities without using a stimulus intensity that produces unacceptable twitching artifact (6,20); this did not seem to be problematic in our patients.…”
Section: Discussionmentioning
confidence: 52%
“…It was previously reported that in approximately 6%e10% of patients undergoing transcranial MEP monitoring without neuromuscular blockade, recording was impossible during microsurgery because of electrostimulation-induced muscle contraction or failure to elicit a baseline motor response from muscles that were intact in the preoperative period (20,27). Quiñones-Hinojosa et al (22) reported good success obtaining transcranial MEPs in a small group (N ¼ 30) of patients with aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations